Adhesive, lithium battery negative electrode slurry, lithium battery negative electrode and lithium battery

Through the use of high-molecular-weight acrylic copolymer adhesive, the problems of insufficient molecular weight and weak cohesion in lithium batteries are solved, the energy density and cycling performance of lithium-ion batteries are improved, and the stability and safety of electrodes are enhanced.

CN119307199APending Publication Date: 2025-01-14JIANGSU DAOYING TECH CO LTD

Patent Information

Application Number
CN202411411660.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-07
Filing Date
2024-10-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The molecular weight of existing lithium battery adhesives is not high enough and the cohesive force is weak, which cannot effectively suppress the expansion of the highly expanded silicon carbon negative electrode, resulting in insufficient safety of the battery under high power charge and discharge and high temperature.

Method used

Using high molecular weight acrylic copolymer binder, by adjusting the neutralization degree and monomer ratio, an aqueous acrylic copolymer binder with a weight average molecular weight of more than 700,000 was prepared for use in the negative electrode of lithium batteries, combined with a specific solution polymerization method. and initiator to form an electrode structure with high peel strength and low internal resistance.

Benefits of technology

It improves the energy density and circulation performance of lithium-ion batteries, reduces the internal resistance of the battery, enhances the structural stability and safety of the electrodes, and reduces the fire risk caused by temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307199A_ABST
    Figure CN119307199A_ABST
Patent Text Reader

Abstract

The invention discloses an adhesive, lithium battery negative electrode slurry, a lithium battery negative electrode and a lithium battery. The adhesive comprises an acrylic copolymer; polymeric monomers of the acrylic copolymer comprise an acrylic monomer, an acrylonitrile monomer, an acrylamide monomer and a selective acrylate monomer; the preparation method of the acrylic acid copolymer comprises the following steps: mixing an acrylic acid monomer with water, adding alkali for neutralization until the neutralization degree is greater than or equal to 50% and less than 100%, then adding an acrylamide monomer and an acrylonitrile monomer, selectively adding an acrylic ester monomer, heating to a reaction temperature in a protective atmosphere, and carrying out a reaction for 2-4 hours to obtain the acrylic acid copolymer. Adding an initiator to initiate an aqueous solution polymerization reaction to generate an acrylic copolymer; practice shows that the binder has higher molecular weight and better electrical performance, when the binder is applied to the negative electrode of the lithium battery, excellent binding power and battery cycle performance can be obtained while the use amount of the binder is reduced, and the binder can be used for preparing the lithium battery, related electrodes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to an adhesive, a lithium battery negative electrode slurry, a lithium battery negative electrode and a lithium battery. Background Art

[0002] Lithium-ion batteries (also known as lithium batteries) have high energy density and long cycle life, and are widely used in portable electronic devices, electric vehicles, energy storage and other fields. Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators, electrolytes, and shells. Their working principle is to store and release electrical energy through the redox reaction of reversible embedding / de-embedding of lithium ions in electrode active materials. The preparation method of the positive and negative electrodes of lithium-ion batteries is to mix the positive electrode active material or the negative electrode active material with an electrode adhesive, a conductive agent, a dispersion medium, etc. into a slurry, apply it to the corresponding current collector foil, and obtain it through drying, rolling, cutting and other processing techniques. It can be seen that the adhesive plays a key role in the preparation of electrodes.

[0003] Water-based adhesives are safe, pollution-free, do not need to recycle solvents, and are easy to operate, making them the first choice for negative electrode adhesives for lithium-ion batteries. Currently, commonly used water-based adhesives are SBR (styrene-butadiene rubber emulsion), copolymer PAA (polyacrylic acid) solution, and copolymer PAN (polyacrylonitrile) emulsion.

[0004] The SBR / CMC system focuses on point-to-point bonding between particles, and the pole piece rebounds after compaction and the expansion rate increases after liquid injection.

[0005] The copolymerized PAA solution is a chain polymer water-based adhesive, which is weakly acidic, colorless or light yellow liquid. Compared with the SBR / CMC system, PAA belongs to line bonding, has a higher degree of anchoring to particles, and has a stronger cohesive force of the pole piece, which is conducive to structural stability. In addition, the copolymerized PAA solution system binder has the following advantages: it contains a higher proportion of strong polar groups such as sodium carboxylate, which has a better bonding effect on the current collector; the volume thermal expansion coefficient is small, the thermal diffusion coefficient is large, and its battery is safer than PVDF-based lithium batteries when used at high power charging and discharging and high temperature, and the possibility of safety accidents due to volume expansion is smaller, which can reduce the probability of fire caused by temperature concentration; the modified water-based acrylic copolymer adhesive is used for the positive and negative electrodes of lithium batteries, which can better inhibit the volume expansion of active materials, form a more stable thin SEI film, effectively block the corrosion of electrolyte to active materials, reduce the impedance of the electrode, especially the charge transfer impedance, and increase the lithium ion diffusion rate, which is crucial to improving the performance of the battery. Currently, copolymer PAA solution has been industrialized, but it generally has problems such as insufficient molecular weight, weak cohesion, and insufficient Young's modulus, and cannot effectively inhibit the expansion of high-expansion silicon-carbon negative electrodes.

[0006] Chinese patent CN112680147A discloses a battery adhesive, which contains a polymer with both hydrophilic units and hydrophobic units, the weight percentage of hydrophilic monomers and lipophilic monomers is 30-70%: 70-30%, and in the polymer, medium and low molecular weight polymers account for less than 5% of the total polymer, and the molecular weight of the medium and low molecular weight polymers is ≤100,000. Although the molecular weight is improved to a certain extent in the patent, the precipitation process used in the patent is used for preparation, and the precipitation process will limit the further increase of the molecular weight of the polymer, and water washing is required to remove the oligomers, resulting in a large amount of washing wastewater. Summary of the invention

[0007] The technical problem actually solved by the present invention is to provide an adhesive with higher molecular weight and better electrical properties for one or more deficiencies in the prior art. When used on the negative electrode of a lithium battery, the amount of adhesive used can be reduced while still achieving excellent bonding strength and battery cycle performance.

[0008] The present invention also provides a lithium battery negative electrode slurry containing the above-mentioned adhesive, a lithium battery negative electrode prepared by using the lithium battery negative electrode slurry, and a lithium battery including the lithium battery negative electrode.

[0009] In order to achieve the above object, a technical solution adopted by the present invention is:

[0010] A water-based acrylic copolymer adhesive, comprising an acrylic copolymer having a weight average molecular weight of 700,000 or more,

[0011] The polymerized monomers of the acrylic copolymer include, by weight percentage, 30-80% acrylic acid monomers, 10-55% acrylonitrile monomers, 10-50% acrylamide monomers, and 0-35% acrylate monomers;

[0012] The acrylic copolymer is prepared by first mixing water and acrylic monomers, adjusting the neutralization degree to be greater than or equal to 50% and less than 100%, and then polymerizing the mixture with acrylonitrile monomers, acrylamide monomers and selectively acrylate monomers to obtain an aqueous solution of the acrylic copolymer.

[0013] Another technical solution provided by the present invention is: an adhesive, the adhesive comprising an acrylic copolymer; the polymerized monomers of the acrylic copolymer comprise, by weight percentage, 30-80% of acrylic acid monomers, 10-55% of acrylonitrile monomers, 10-50% of acrylamide monomers, and 0-35% of acrylate monomers;

[0014] The preparation method of the acrylic acid copolymer comprises:

[0015] Acrylic acid monomers and water are mixed, alkali is added for neutralization so that the neutralization degree is greater than or equal to 50% and less than 100%, and then acrylamide monomers, acrylonitrile monomers and optionally acrylate monomers are added. Under a protective atmosphere, after heating to the reaction temperature, an initiator is added to initiate an aqueous solution polymerization reaction to generate the acrylic acid copolymer.

[0016] According to some embodiments of the present invention, the neutralization degree is 50-90%. A certain neutralization degree is beneficial to reducing the intermolecular agglomeration effect and obtaining a polymer with a higher molecular weight.

[0017] In some specific embodiments, the degree of neutralization is 65-85%.

[0018] According to some embodiments of the present invention, the weight average molecular weight of the acrylic copolymer is 700,000 to 2.2 million, and further, the weight average molecular weight of the acrylic copolymer is 1.3 million to 2.2 million.

[0019] According to some embodiments of the present invention, the number average molecular weight of the acrylic copolymer is 200,000 to 650,000.

[0020] According to some embodiments of the present invention, the polymerizable monomers include, by weight percentage, 35-70% acrylic acid monomers, 10-50% acrylonitrile monomers, 10-30% acrylamide monomers and 0-10% acrylate monomers.

[0021] In some specific embodiments, the polymerizable monomers include, by weight percentage, 42-60% acrylic acid monomers, 20-35% acrylonitrile monomers, 10-30% acrylamide monomers and 0-10% acrylate monomers.

[0022] Furthermore, in terms of percentage by weight, the polymerizable monomers include: 42-60% acrylic acid monomers, 20-35% acrylonitrile monomers, 10-20% acrylamide monomers and 0-10% acrylate monomers.

[0023] According to some specific and preferred aspects of the present invention, the polymerizable monomers include, by weight percentage, 30-60% acrylic acid monomers, 20-35% acrylonitrile monomers, 10-30% acrylamide monomers and 0-10% acrylate monomers.

[0024] According to some embodiments of the present invention, the aqueous solution polymerization is carried out in the presence of an initiator, and the amount of the initiator used is 0.1 to 2% of the total amount of the polymerization monomers.

[0025] In some specific embodiments, the amount of the initiator is 0.2-1.2% of the total amount of the polymerization monomers. Further, the amount of the initiator is 0.5-0.9% of the total amount of the polymerization monomers.

[0026] In some specific embodiments, the initiator is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, lauroyl peroxide, azobisisobutyronitrile, and azobisisoheptylonitrile.

[0027] According to some embodiments of the present invention, the preparation method of the acrylic copolymer includes mixing acrylic monomers and water, adding alkali for neutralization and making the neutralization degree greater than or equal to 50% and less than 100%, then adding acrylamide monomers, acrylonitrile monomers and selectively adding acrylate monomers, heating to the reaction temperature under a nitrogen or inert gas (including but not limited to helium, argon, etc.) atmosphere, adding an initiator to initiate an aqueous solution polymerization reaction, and obtaining an aqueous solution of the acrylic copolymer.

[0028] In some specific embodiments, the base is one or a combination of sodium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, potassium hydroxide.

[0029] In some specific embodiments, the base is added in an amount such that the neutralization degree of the acrylic monomer is greater than or equal to 50% and less than 100%.

[0030] In some specific embodiments, the reaction temperature is 40-70°C.

[0031] In some specific embodiments, the initiator is directly added or added dropwise in the form of an aqueous solution or a monomer solution.

[0032] In some specific embodiments, the solid content of the aqueous acrylic copolymer adhesive or the adhesive is 2-6%.

[0033] In some specific embodiments, after the polymerization reaction is completed, the pH value of the system is adjusted to 7-8.

[0034] In some specific embodiments, the acrylic monomer is selected from one or more combinations of compounds represented by formula (I), CR1R2 = CH(R3)-COOH(I), wherein R1, R2, and R3 are independently selected from H, methyl, ethyl, or propyl.

[0035] Furthermore, the acrylic monomer is one or a combination of acrylic acid and methacrylic acid.

[0036] Furthermore, the acrylic monomer is a combination of acrylic acid and / or methacrylic acid and propylene sulfonic acid, and the mass ratio of the acrylic acid and / or methacrylic acid to the propylene sulfonic acid is 1:0.8-1.2.

[0037] In some specific embodiments, the acrylonitrile monomer is a combination of one or more compounds selected from the compounds represented by formula (II), CR4R5 = CH(R6)-CN(II), wherein R4, R5, and R6 are independently selected from H, methyl, ethyl or propyl.

[0038] Furthermore, the acrylonitrile monomer is one or a combination of acrylonitrile and methacrylonitrile.

[0039] In some specific embodiments, the acrylamide monomer is a combination of one or more compounds selected from the group consisting of: CR7R8=CH(R9)-C(=O)-NR 10 R 11 (III), wherein R7, R8, and R9 are independently selected from H, methyl, ethyl, or propyl, and R 10 , R 11 independently selected from H, methyl, ethyl, propyl, -C(CH3)2-CH2-C(=O)-CH3, -CH2-OR 12 , -R 13 -OH, -R 14 -OR 15 , -R 16 -OR 17 -COOH, R 12 , R 13 , R 14 , R 15 , R 16 , R 17 Independently selected from C 1-10 Furthermore, C 1-10 The alkyl group includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, heptyl, octyl, nonyl, decyl, and the like.

[0040] Furthermore, the acrylamide monomer is selected from one or a combination of acrylamide, N-methylacrylamide, N-ethylacrylamide, N-butylacrylamide, 2-methylacrylamide, diacetoneacrylamide, N-methoxymethylacrylamide, N-isopropyloxymethylacrylamide, N-hydroxymethylacrylamide, N-butoxymethylacrylamide, N-isobutyloxymethylacrylamide, N-octyloxymethylacrylamide, and N-carboxymethoxymethylacrylamide.

[0041] In some specific embodiments, the acrylic acid ester monomer is a combination of one or more compounds selected from the group consisting of compounds represented by formula (IV), CR 18 R 19 =CH(R 20 )-C(=O)-OR 21 (IV), where R 18 , R 19 , R 20 are independently selected from H, methyl, ethyl or propyl, R 21 Selected from C 1-10 Furthermore, C 1-10 The alkyl group includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, 2-ethylhexyl, heptyl, octyl, nonyl, decyl, and the like.

[0042] Further, the acrylic acid ester monomer is at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, and 2-ethylhexyl acrylate; and methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, and 2-ethylhexyl methacrylate.

[0043] Another technical solution provided by the present invention is: use of the above-mentioned water-based acrylic copolymer adhesive or adhesive in the preparation of lithium battery electrodes.

[0044] Another technical solution provided by the present invention is a negative electrode slurry for a lithium battery, comprising a binder, a negative electrode active material and a conductive agent, wherein the binder is the above-mentioned aqueous acrylic copolymer binder or the above-mentioned binder.

[0045] Furthermore, the mass ratio of the binder, the negative electrode active material and the conductive agent is 0.5-1.5:92-98:1, wherein the binder is calculated by dry weight in the solution.

[0046] Furthermore, the lithium battery negative electrode slurry also includes a thickener, and the mass ratio of the thickener to the conductive agent is 0.1 to 0.8:1.

[0047] Furthermore, the negative electrode active material is one or a combination of artificial graphite, natural graphite, and hard carbon.

[0048] Furthermore, the conductive agent is one or a combination of carbon black, carbon nanotubes, and graphene.

[0049] Another technical solution provided by the present invention is a lithium battery negative electrode, comprising a substrate and a coating formed on the substrate, wherein the coating is formed by coating a slurry on the substrate and drying the slurry, and the slurry is the lithium battery negative electrode slurry described above.

[0050] Furthermore, the substrate is copper foil or a copper-PET-copper composite current collector.

[0051] Another technical solution provided by the present invention is: a lithium battery comprising the lithium battery negative electrode described above.

[0052] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0053] The present invention uses acrylic monomers as the main skeleton, introduces appropriate amounts of acrylonitrile monomers and highly polar acrylamide monomers, and selectively introduces acrylate monomers, and combines a specific solution polymerization method to synthesize an aqueous solution adhesive of a linear acrylic copolymer. The aqueous solution adhesive has a higher molecular weight and is used in the negative electrode of a lithium battery. The adhesive has high peel strength, and the internal resistance of the battery is lowered by reducing the amount of binder added, thereby improving the energy density and cycle performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 The molecular weight test results of the adhesives of Comparative Examples 1 to 5;

[0055] Figure 2 The molecular weight test results of the adhesives of Examples 1 to 8;

[0056] Figure 3 This is an appearance diagram of the water-based acrylic copolymer adhesive of Example 1. DETAILED DESCRIPTION

[0057] The existing adhesive with acrylic acid as the main structure has problems such as low bonding force and poor electrical properties. The present invention uses an aqueous solution polymerization method to use acrylic monomers as the main skeleton, introduces appropriate amounts of acrylonitrile monomers and strongly polar acrylamide monomers, and selectively introduces acrylate monomers to prepare a high molecular weight water-based acrylic copolymer adhesive. On the one hand, PAA (polyacrylic acid) as an adhesive will hardly swell in the carbonate solvent of the electrolyte, and the electrode sheet structure is stable during the charge and discharge process. The carboxyl content in its structure is higher than that of CMC, and it can form a strong hydrogen bond with active material materials containing hydroxyl groups on the surface, promote the formation of a more uniform coating on the electrode surface than CMC, and can form a denser film in the electrode sheet, increase the electrical contact between the active material and the current collector, and has excellent tensile mechanical strength, which is conducive to mechanical processing; on the second hand, it is found in practice that the neutralization degree of -COOH in PAA greatly affects its performance as a binder. The analysis shows that after PAA is dissolved in water, it is easy to form an intermolecular aggregate structure due to the strong intermolecular carboxyl hydrogen bonding force. A certain amount of PAA is neutralized with alkali to prepare PAH-M salt. The electrostatic repulsion between the carboxyl salt groups improves the stretchability of the molecular chain, which is beneficial to reduce the intermolecular aggregation effect and increase the solubility of the polymer, which is beneficial to obtain a polymer with a higher molecular weight; thirdly, the introduced acrylonitrile monomer contains a strong polar nitrile functional group, which can form hydrogen bonding forces and dipole forces with the surrounding materials. As a binder, it is beneficial to improve the stability of the electrode sheet structure and the wettability of the electrolyte; fourthly, when the introduced acrylamide monomer is used as a binder, it can form a stable polymer structure through cross-linking reaction, and the covalent bond formed with the active substance is beneficial to inhibit the swelling of polar solvents.

[0058] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0059] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0060] Example 1

[0061] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein:

[0062] The acrylic monomer is acrylic acid;

[0063] The acrylamide monomer is acrylamide;

[0064] The acrylonitrile monomer is acrylonitrile;

[0065] The initiator is ammonium persulfate.

[0066] Prepared by the following method:

[0067] Add 270 parts of deionized water to the reaction container, start stirring, add acrylic monomer, neutralize the acrylic monomer with sodium hydroxide to a neutralization degree of 80%, then add acrylamide monomer and acrylonitrile monomer, heat to 60°C under nitrogen atmosphere and keep the temperature constant, then drop 30 parts of 2% ammonium persulfate initiator solution within 1 hour, react for 6 hours, then adjust the pH to 7 with sodium hydroxide, add water to adjust the solid content to 6%, and obtain a water-based acrylic copolymer adhesive, which has the appearance as shown below: Figure 3 Show.

[0068] Example 2

[0069] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein the raw materials are different from those in Example 1 in that benzoyl peroxide is used as the initiator.

[0070] The preparation method is basically the same as that of Example 1.

[0071] Example 3

[0072] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein the raw materials are different from those in Example 1 in that acrylic acid is neutralized with ammonia water to a neutralization degree of 80%.

[0073] The preparation method is basically the same as that of Example 1.

[0074] Example 4

[0075] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein the raw materials are different from those in Example 1 in that the acrylamide monomer is a combination of acrylamide and diacetone acrylamide in a mass ratio of 10:1.

[0076] Example 5

[0077] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein the raw materials are different from those in Example 1 in that the acrylic ester monomer is butyl acrylate.

[0078] The preparation method is basically the same as that of Example 1, and the acrylic acid ester monomers are added together with the acrylamide monomers and the acrylonitrile monomers.

[0079] Example 6

[0080] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein the raw materials are different from those in Example 1 in that the degree of neutralization is 50%.

[0081] Example 7

[0082] The water-based acrylic copolymer adhesive provided in this embodiment has a raw material formula as shown in Table 1, wherein the raw materials are different from those in Example 1 in that: the neutralization degree is 60%; the acrylic monomer is a combination of methacrylic acid and propylene sulfonic acid in a mass ratio of 1:1; and the acrylamide monomer is N-ethylacrylamide.

[0083] Example 8

[0084] The raw material formula of the water-based acrylic copolymer adhesive provided in this embodiment is shown in Table 1, wherein the raw materials are different from those in Example 1 in that the neutralization degree is 90%, the acrylonitrile monomer is methacrylonitrile, and the acrylamide monomer is N-hydroxymethyl acrylamide.

[0085] Comparative Examples 1-2

[0086] Comparative Example 1 uses AONE from Shenzhen Yanyi New Materials Co., Ltd., which is a linear ultra-high molecular weight, and is a high molecular weight water-soluble acrylic copolymer; Comparative Example 2 uses LA136D water-based adhesive from Sichuan Yindile Materials Technology Group Co., Ltd., which is an aqueous solution of an acrylic acid derivative copolymer.

[0087] Comparative Example 3

[0088] The raw material formula of the adhesive of Comparative Example 3 is shown in Table 2, wherein the neutralization degree is not adjusted during preparation, and the rest is the same as Example 3.

[0089] Comparative Example 4

[0090] The raw material formula of the adhesive of Comparative Example 4 is shown in Table 2, wherein during preparation, the neutralization degree of acrylic acid is adjusted to 100% with sodium hydroxide, and the rest is the same as in Example 3.

[0091] Comparative Example 5

[0092] The raw material formula of the adhesive of Comparative Example 5 is shown in Table 2, wherein during preparation, the neutralization degree of acrylic acid is adjusted to 30% with sodium hydroxide, and the rest is the same as Example 3.

[0093] Table 1 Polymerization monomer composition of the adhesive of Examples 1 to 8 (by weight)

[0094]

[0095]

[0096] Table 2 shows the polymerized monomer compositions of the adhesives of Comparative Examples 3 to 5 (by weight)

[0097]

[0098] Performance Testing

[0099] 1. Molecular weight and viscosity test

[0100] The molecular weight and viscosity of the adhesives of Examples 1 to 8 and Comparative Examples 1 to 5 were tested (tested at 25° C.) using an Agilent 1260 Infinity II multi-detector GPC / SEC system. The results are shown in Tables 3 to 4, and Figure 1 , Figure 2 The molecular weight distribution graphs of Comparative Examples 1 to 5 and Examples 1 to 8 are shown.

[0101] Table 3 shows the molecular weight and viscosity test results of the adhesives of Examples 1 to 8.

[0102]

[0103] Table 4 shows the molecular weight test results of the adhesives of Comparative Examples 1 to 5.

[0104]

[0105] 2. Peel force test

[0106] Test method: According to the formula, graphite, conductive agent SP, CMC, SBR and adhesive are prepared into slurry in a mass ratio of 96.6:1:0.5:0.8:1.1 (where SBR and adhesive are both measured by dry weight), and water is added to adjust the slurry viscosity to 4000±200mpa·s. The mixed slurry is coated on the copper foil by a battery coating machine and dried at 120°C. The dried electrode is rolled to obtain a negative electrode with a coating thickness of 80μm, and then adhered to a 50mm×150mm mirror steel plate for peeling force test with a 25mm wide double-sided tape, and cut into a 25mm×120mm rectangle, fixed on a stretching machine, and a 180-degree peeling force test is performed at a stretching speed of 5mm / min. The results are shown in Tables 5 and 6.

[0107] Table 5 shows the peeling force test results of the adhesives of Examples 1 to 8.

[0108]

[0109] Table 6 shows the peeling force test results of the adhesives of Comparative Examples 1 to 5.

[0110]

[0111] 3. Electrical performance test results

[0112] 3.1 Cycle performance

[0113] 1C constant current charging to voltage 3.65V, and constant voltage at 3.65V to current cutoff of 0.05C; let stand for 20 minutes, then use 1C constant current discharge, cutoff voltage is 2.5V, let stand for 20 minutes, complete a cycle. The results are shown in Table 7-Table 8.

[0114] Table 7 shows the cycle test results of the adhesives of Examples 1-8

[0115]

[0116] Table 8 shows the cycle test results of the adhesives of Comparative Examples 1-5

[0117]

[0118] 3.2、DCR test (25℃3C-30s@50%SOC)

[0119] The battery was charged to 3.65V at a constant current of 1C, charged at a constant voltage of 3.65V to a current cutoff of 0.05C, left for 1h, discharged at a constant current of 1C for 30min, the SOC was adjusted to 50%, left for 1h, and then discharged at a constant current of 3C for 30s. The DCR value was obtained by the calculation formula. The results are shown in Tables 9 and 10.

[0120] Table 9 shows the DCR test results of the adhesives of Examples 1-8

[0121]

[0122] Table 10 shows the DCR test results of the adhesives of Comparative Examples 1-5.

[0123]

[0124] It can be seen from Table 7 and Table 8 that the products of Examples 1 to 8 of the present invention have good cycle performance. It can be seen from Table 9 and Table 10 that the products of Examples 1 to 8 of the present invention have relatively small impedance.

[0125] As can be seen from Comparative Example 3, under the condition of complete non-neutralization, the molecular weight of Comparative Example 3 is relatively low, and its peeling force, cycle performance and impedance are all poor, indicating that if the neutralization degree after the addition of the acrylic monomer is not actively controlled during the preparation process, it will significantly affect the various properties of the adhesive generated by the reaction, and present a negative impact. For Comparative Examples 4-5, although the neutralization degree is regulated, when the acrylic monomer is completely neutralized or the neutralization degree is low, although the weight average molecular weight is improved compared with Comparative Example 3, the number average molecular weight is still insufficient, especially in terms of peeling force, cycle performance and impedance, which are all poor, indicating that the degree of regulation of the neutralization degree will also affect the various properties of the adhesive.

[0126] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0127] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. An adhesive, characterized in that: The adhesive comprises an acrylic copolymer; the polymerized monomers of the acrylic copolymer comprise, by weight percentage, 30 to 80% of acrylic acid monomers, 10 to 55% of acrylonitrile monomers, 10 to 50% of acrylamide monomers, and 0 to 35% of acrylate monomers; The preparation method of the acrylic acid copolymer comprises: Acrylic acid monomers and water are mixed, alkali is added for neutralization so that the neutralization degree is greater than or equal to 50% and less than 100%, and then acrylamide monomers, acrylonitrile monomers and optionally acrylate monomers are added. Under a protective atmosphere, after heating to the reaction temperature, an initiator is added to initiate an aqueous solution polymerization reaction to generate the acrylic acid copolymer.

2. The adhesive according to claim 1, characterized in that: The neutralization degree is 50-90%.

3. The adhesive according to claim 1, characterized in that: The reaction temperature is 40-70°C.

4. The adhesive according to claim 1, characterized in that: The protective atmosphere is formed by introducing one or more of nitrogen, helium and argon; and / or the initiator is directly added or added dropwise in the form of an aqueous solution or a monomer solution, and the amount of the initiator is 0.1-2% of the total amount of the polymerization monomers.

5. The adhesive according to claim 1, characterized in that: The amount of the initiator is 0.2-1.2% of the total amount of the polymerization monomers; and / or the initiator is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, lauroyl peroxide, azobisisobutyronitrile and azobisisoheptylonitrile.

6. The adhesive according to claim 1, characterized in that: The added amount of the base is such that the neutralization degree of the acrylic monomer is greater than or equal to 50% and less than 100%; and / or the base is one or a combination of sodium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, potassium hydroxide.

7. The adhesive according to claim 1, characterized in that: The acrylic monomer is selected from one or more combinations of compounds represented by formula (I), CR1R2=CH(R3)-COOH(I), wherein R1, R2, and R3 are independently selected from H, methyl, ethyl or propyl.

8. The adhesive according to claim 1 or 7, characterized in that: The acrylic monomer is acrylic acid and / or methacrylic acid; or, the acrylic monomer is a combination of acrylic acid and / or methacrylic acid and propylene sulfonic acid, and the mass ratio of the acrylic acid and / or methacrylic acid to the propylene sulfonic acid is 1:0.8-1.

2.

9. The adhesive according to claim 1, characterized in that: The acrylonitrile monomer is a combination of one or more compounds selected from the group consisting of compounds represented by formula (II), CR4R5=CH(R6)-CN(II), wherein R4, R5, and R6 are independently selected from H, methyl, ethyl, or propyl.

10. The adhesive according to claim 1 or 9, characterized in that: The acrylonitrile monomer is acrylonitrile and / or methacrylonitrile.

11. The adhesive according to claim 1, characterized in that: The acrylamide monomer is a combination of one or more compounds selected from the group consisting of the compounds shown in formula (III): CR7R8=CH(R9)-C(=O)-NR 10 R 11 (III), wherein R7, R8, and R9 are independently selected from H, methyl, ethyl, or propyl, and R 10 , R 11 independently selected from H, methyl, ethyl, propyl, -C(CH3)2-CH2-C(=O)-CH3, -CH2-OR 12 , -R 13 -OH, -R 14 -OR 15 , -R 16 -OR 17 -COOH, R 12 , R 13 , R 14 , R 15 , R 16 , R 17 Independently selected from C 1-10 alkyl.

12. The adhesive according to claim 1 or 11, characterized in that: The acrylamide monomer is one or a combination of acrylamide, N-methylacrylamide, N-ethylacrylamide, N-butylacrylamide, 2-methylacrylamide, diacetoneacrylamide, N-methoxymethylacrylamide, N-isopropyloxymethylacrylamide, N-hydroxymethylacrylamide, N-butoxymethylacrylamide, N-isobutyloxymethylacrylamide, N-octyloxymethylacrylamide, and N-carboxymethoxymethylacrylamide.

13. The adhesive according to claim 1, characterized in that: The acrylic acid ester monomer is a combination of one or more compounds selected from the group consisting of compounds represented by formula (IV), CR 18 R 19 =CH(R 20 )-C(=O)-OR 21 (IV), where R 18 , R 19 , R 20 are independently selected from H, methyl, ethyl or propyl, R 21 Selected from C 1-10 alkyl.

14. The adhesive according to claim 1 or 13, characterized in that: The acrylic acid ester monomer is at least one selected from methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, and 2-ethylhexyl acrylate; methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, and 2-ethylhexyl methacrylate.

15. The adhesive according to claim 1, characterized in that: The weight average molecular weight of the acrylic copolymer is 700,000 to 2.2 million; and / or the number average molecular weight of the acrylic copolymer is 200,000 to 650,000.

16. The adhesive according to claim 1, characterized in that: Calculated by weight percentage, the polymerizable monomers include: 30-60% acrylic acid monomers, 20-35% acrylonitrile monomers, 10-30% acrylamide monomers and 0-10% acrylate monomers.

17. A negative electrode slurry for a lithium battery, comprising a binder, a negative electrode active material and a conductive agent, characterized in that: The adhesive is the adhesive according to any one of claims 1 to 16.

18. A negative electrode for a lithium battery, comprising a substrate and a coating formed on the substrate, wherein the coating is formed by coating a slurry on the substrate and drying the coating, wherein: The slurry is the lithium battery negative electrode slurry according to claim 17.

19. A lithium battery, characterized in that: A lithium battery negative electrode comprising the negative electrode of claim 18.

Citation Information

Patent Citations

  • Preparation method of binder for battery

    CN112680147A

Cited By

  • Adhesive and preparation method thereof, negative pole piece, battery and electric equipment

    CN120005539A

  • Adhesive and its preparation method, negative electrode sheet, battery and electrical equipment

    CN120005539B

  • Water-based negative electrode binder as well as preparation method and application thereof

    CN121343516A

  • Copolymer for lithium ion battery, negative pole piece and preparation and application methods of copolymer and negative pole piece

    CN121471417A

  • Emulsion type binder as well as preparation method and application thereof

    CN121950213A